Notes sur le mobilier funéraire de Thoutmosis IV - Renaud Pietri (Les Cahiers de l'École du Louvre)
The tomb of Thutmose IV (KV 43), excavated in the early twentieth century by Howard Carter, contained two leather-scabbard fragments, which probably attested to the presence of daggers among the grave goods of the 18th-dynasty king. The present article suggests, after a short description of the two objects published for the first time in 1904, that they are similar to a particular type of dagger discovered in the Nubian city of Kerma in particular. A discussion of the reasons that might have led an 18th-century king to take Nubian daggers to the grave with him follows.